2017
DOI: 10.1037/fsh0000242
|View full text |Cite
|
Sign up to set email alerts
|

Reducing barriers to mental health care for student-athletes: An integrated care model.

Abstract: Research suggests that National Collegiate Athletic Association (NCAA) Division I student-athletes have higher levels of stress and other behavioral health issues, including substance use, than nonathletes. For several reasons, student-athletes may be less likely to admit to behavioral health issues and seek mental health care. Integrated care is a model of care that integrates behavioral health into a medical practice. This article explores the newly released NCAA Best Mental Health Practice guidelines and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 25 publications
3
39
2
2
Order By: Relevance
“…According to data from the National College Health Assessment surveys, about 31% of male and 48% of female National Collegiate Athletic Association (NCAA) student-athlete respondents from 92 different institutions reported either depression or anxiety symptoms each year of the 2008 and 2012 academic years due to the many aforementioned challenges and stressors (ACHA, 2018). A more recent study reports that of the approximately 400,000 NCAA student-athletes participating in sports at more than 1,000 member institutions across the United States (U.S.), rates of depression range 15.6% to 21.0%, and freshman are at greater risk than other collegiate class years to develop depressive symptoms (Sudano, Collins, & Miles, 2017). Evidence has also shown that due to the extensive time demands, pressures, and added stressors, collegiate athletes are at significant risk for other mental health related problems such as clinical or subclinical eating disorders, sleep disturbances, gambling addictions, substance abuse, mood disorders, and even suicide (Moreland, Coxe, & Yang, 2017).…”
Section: Student-athlete Mental Health and Sport Psychology In Collegementioning
confidence: 99%
See 4 more Smart Citations
“…According to data from the National College Health Assessment surveys, about 31% of male and 48% of female National Collegiate Athletic Association (NCAA) student-athlete respondents from 92 different institutions reported either depression or anxiety symptoms each year of the 2008 and 2012 academic years due to the many aforementioned challenges and stressors (ACHA, 2018). A more recent study reports that of the approximately 400,000 NCAA student-athletes participating in sports at more than 1,000 member institutions across the United States (U.S.), rates of depression range 15.6% to 21.0%, and freshman are at greater risk than other collegiate class years to develop depressive symptoms (Sudano, Collins, & Miles, 2017). Evidence has also shown that due to the extensive time demands, pressures, and added stressors, collegiate athletes are at significant risk for other mental health related problems such as clinical or subclinical eating disorders, sleep disturbances, gambling addictions, substance abuse, mood disorders, and even suicide (Moreland, Coxe, & Yang, 2017).…”
Section: Student-athlete Mental Health and Sport Psychology In Collegementioning
confidence: 99%
“…Despite the growing population of student-athletes who can benefit from support of a sport psychologist, only 40% of NCAA Division I university athletic training rooms use screening instruments to assess student-athletes for mental health issues, i.e., depression, anxiety, eating disorders, substance use, mood disorders, and attention deficit hyperactivity (Sudano & Miles, 2017). Some athletic trainers surveyed in a study reported that they lacked a formal mental health referral process inside their athletic department (Clement, Granquist, & Arvinen-Barrow, 2013).…”
Section: Student-athlete Mental Health and Sport Psychology In Collegementioning
confidence: 99%
See 3 more Smart Citations